Fidusia: Kajian Terhadap Perjanjian Jaminan di Bawah Tangan - Siti Nurhayati (Justicia Islamica, 2007)
This study aims to analyze the concept of fiduciary in a handwritten collateral agreement and its implications in legal practice in Indonesia. This study explores the legal validity, executory power, and legal risks arising from unregistered fiduciary agreements. The research method used is library research with a juridical-normative approach. The research sources include the Fiduciary Guarantee Law, court decisions, and relevant legal literature. The results of the study show that underhand fiduciary agreements have weaknesses in the aspect of legal protection for creditors, especially in the process of collateral execution. The non-registration of fiduciary rights results in the inability to directly enforce executory rights, creating the potential for legal disputes. This study emphasizes the importance of registering a trust to provide legal certainty and stronger protection for parties in collateral agreements.